Causes, Effects, and Practical Methods of Harmonic Reduction in Iranian Cement Factories with a Focus on Plant Development - Mehdi Eslamian Koupaie (ITEGAM-JETIA)
Cement factories in Iran are considered among the oldest industries. Due to favorable domestic and international markets, these plants have pursued development, whether willingly or unwillingly. Development involves improving the existing structure to enhance efficiency and adding production lines parallel to the old ones. In this situation, the presence of very large nonlinear loads in these industries, which are mostly formed by high-power variable-speed electric drives, has always caused serious problems due to harmonic distortions imposed on the factory and distribution lines. These effects should be considered in various sections when developing and designing new electrical systems. Despite various studies on this subject, none has presented a comprehensive approach specifically for this industry. This article delves into a thoroughly practical and empirical examination of the causes and consequences stemming from harmonics, alongside the constraints posed by standards. It also scrutinizes implementable techniques for solving harmonic-related problems and mitigating their effects with a focus on the development outlook of cement factories.